Level of Protein Metabolism in Cows in Uzbekistan Conditions (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article presents the results of a study of blood serum of heifers and cows of different ages depending on the period of pregnancy, lactation, type of feeding and environmental conditions. The time of the most pronounced disorders of protein metabolism in cows was determined. The parameters of protein metabolism characteristic of healthy and sick cows with protein metabolism disorders under conditions of silage-concentrate and hay-concentrate types of feeding have been established.